Game-Based Development Using the Hannafin and Peck Model for the Tajwid’s Learning Media - Nazliati; Alfiatunnur; Rita Sari (International Journal of Basic Educational Research, 2024)
The pedagogical imperative to enhance Tajweed proficiency, a fundamental Islamic educational tenet, necessitates innovative teaching methodologies, especially for learners at the concrete operational stage. This study introduces "Ludo Listas Tajwid" (Lolita), a pioneering game-based educational media designed to ameliorate the learning trajectory of Tajweed. The research developed and evaluated Lolita to ascertain its efficacy and applicability in the pedagogical domain of Quranic recitation. Utilizing the Research and Development (R&D) approach, underpinned by the Hannafin and Peck model, the study meticulously orchestrated the media development phases, incorporating design, development, and evaluation stages. The methodology entailed a comprehensive descriptive data analysis to delineate the media development steps and substantiate its educational value. This iterative process facilitated the refinement and validation of Lolita, ensuring its alignment with educational standards and learning objectives. The findings revealed that Lolita substantially ameliorated the Tajweed learning experience, evidenced by high validation scores: 88% for media, 90.7% for content, and 80% for language proficiency. These metrics underscore the media's pedagogical soundness and its consonance with Tajweed learning objectives. The implications of this research are multifaceted, extending beyond the immediate educational setting. Lolita's success illustrates the potential of game-based learning platforms in engaging students more effectively in religious education, thereby enhancing their learning outcomes. However, the study acknowledges its limitations, including the specific focus on learners in the concrete operational stage and the need for broader empirical validation across varied educational contexts.. The study recommends further research to explore Lolita's scalability and its impact on long-term learning outcomes, aiming to establish a robust evidence base for game-based learning in religious education.